Koefisien Perpindahan Massa pada Ekstraksi Aspal Buton dari Kabungka dan Bau-Bau dengan Pelarut n-Heksan - Suryo Purwono; Bardi Murachman; Dyah Tri Yulianti; dan Suwati (Forum Teknik, 2005)
Butonion  natural  asphalt  can be used for binder in road construction after its impurities were  removed  by  extraction  using  suitable  solvent.  Researches  on  extraction of Butonion asphalt  have been  done. However, most of them  are  explorative  research.This  experiment  tried  to find mass  transfer  coeficient for Butonion  asphalt  extraction.  The mass tronsfer  coefficient  will be  used  in  extraction  tower  design. In  this  experiment,  multi-stage  cross-cwrent  extraction  was  used  using  n-hexane  as  a solvent.  The number  of  stages was  seven.  Bitumen  obtained  was then  distilled to  separate  the  n-hexane. The operation  variables  were  :  size  of  solid,  rotation  and extTaction  time.The  relationship  of the  mass transfer  coefficient with other variables  can  be written  as:The  constant  values  of  Kabungka  asphalt  are  :  K=6.43558x10tt,  a=0.141569, b=0.2825804,  c =1.76857,  d=  -  1.381755,  e=t.636537x102 ;  those  of Bau-Bau  asphalt  are  : K=  6.3x  I0tt'a  = 0.0891,  b=  0.28258,  c=  L7699,  d = -1.3821Keywords  :  extraction,  mass transfer,  Butonion asphalt